Penerapan Thermotherapy Untuk Mengurangi Nyeri Dada Pasien STEMI - Sri Ardini Susmita; Riani Riani; Neneng Fitria Ningsih (Excellent Health Journal, 2025)
Thermotherapy is the application ofheat to the body to reduce pain intensity. This therapy is effectivein reducing both acute and chronic pain, as it can increase blood flowby dilating blood vessels and improve muscle elasticity, thereby reducing muscle stiffness. Thermotherapy is one of the non-pharmacological therapies used toreduce pain in patients with ST ElevationMyocardial Infarction (STEMI) patients. Optimal pain managementis crucial to prevent complications and improve patient comfort.This study used a case study design with a nursing care approachon Mr. N, a 62-year-old man diagnosed with STEMI. The studywas conducted from April 12-14, 2025, in the CVCU RoomArifin Achmad General Hospital, Riau Province. The assessment revealed that the patientexperienced stabbing chest pain radiating to the back, with a pain scale of7. The ECG showed ST elevation. The diagnosis wasacute painrelated to myocardial ischemia due to coronary artery obstruction. The interventions included the administration of thermotherapy.Thermotherapy was applied usinga hot water bottle filled with water at a temperature of 40-43°C and placed on thechest area for 15-20 minutes when the patient felt chest pain and was carried out for 3consecutive days. The pain scale was measured using the Numeric Rating Scale (NRS). After the application of thermotherapy, the pain scale became a 3. It is hoped that thermotherapy can be used as an independent intervention by patients and families if they experience recurrent chest pain due to STEMI.